Features and Outcomes In Utero and after Birth of Fetuses with Myocardial Disease - Vlasta Fesslova; Maurizio Mongiovì; Salvatore Pipitone; Jelena Brankovic; Laura Villa (International Journal of Pediatrics)
Objectives. Ninety-one fetuses with dilated or hypertrophic cardiomyopathy (DCM, HCM) and myocarditis were studied. Results. Group 1 “DCM” included 19 fetuses: 13 with hydrops (FH) and 5 with associated extracardiac anomalies (ECAs) (15.8%). Group 2 “Myocarditis” included twelve fetuses, having 11 with FH. Group 3 “HCM” included sixty fetuses: 26 had associated ECAs, 17 had maternal diabetes, and 17 were “idiopathic”; however, in one case, a metabolic disorder was found postnatally, and 4 had familiarity for HCM. Outcomes. Ten cases opted for termination of pregnancy. Two cases with DCM and 1 with HCM were lost at follow-up. Out of the cases that continued pregnancy, with known follow-up, mortality was 68.75% in Group 1, 63.6% in Group 2, and 31.3% in Group 3 (the majority with severe ECAs). Surviving cases with DCM and myocarditis improved, 2 with HCM worsened, 6 remained stable, and 26 improved or normalized. Conclusions. Our data show more severe prognosis in DCM and myocarditis and forms with severe associated ECAs.